A retrospective cross-sectional study of the associated factors of hyperuricemia in patients with chronic kidney disease. Issue 6 (June 2020) - Guo, Li-Ping; Wang, Qin; Pan, Yu; Wang, Yan-Lin; Zhang, Ze-Jin; Hu, Chun; Ding, Feng; Peng, Ai; Liu, Jun-Yan
Objective: To investigate the prevalence of hyperuricemia in patients at different stages of chronic kidney disease (CKD) and the association of serum uric acid (SUA) with several clinical factors in a retrospective cross-sectional study of non-dialysis CKD patients at two hospitals in Shanghai, China. Methods: The prevalence of hyperuricemia in CKD patients and the association of SUA with other clinical factors were examined using analysis of variance, chi-squared test, multivariate analysis, and other statistical methods. Results: A total of 663 CKD patients were enrolled, of which approximately 52% had hyperuricemia. CKD patients with hyperuricemia had lower hemoglobin and estimated glomerular filtration rate (eGFR) levels but higher blood urea nitrogen, serum creatinine, and serum phosphate levels than those without hyperuricemia. Serum uric acid level was positively associated with age, blood urea nitrogen, serum creatinine, cystatin C, and serum phosphate and negatively associated with hemoglobin and eGFR. In addition, CKD patients with anemia and hyperphosphatemia had a higher prevalence of hyperuricemia than those without anemia or hyperphosphatemia. Conclusions: The prevalence of hyperuricemia increased with CKD progression supporting the use of urate-lowering treatment for patients with CKD stage 1 to 4.